Curbing Promiscuous Sex through the Practice of Fasting: An Islamic Approach - Mansor, Nurul Husna; Abdullah, Raihanah; Mohamad Nor, Azmawaty; Mohammad Jodi, Khairul Hamimah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Promiscuous sex is a social issue that is now rampant and has implications on society that includes an alarming increase in premarital sex among adolescence, the increase in numbers of children out-of-wedlock, rising infidelity cases and divorce rates. To curb the problem of promiscuous sex, Islamic law has recognized the practice of fasting as a practical approach to control sexual desire and fornication. This paper intends to evaluate how the philosophy and practice of fasting in Islam help curb promiscuous sexual behavior. This study employs a qualitative research design using interviews, a content analysis approach that examined various materials sourced from primary and secondary data related to the topic under study. The documents encompass Holy al-Qur’an, al-Hadith, theses, books, and academic journal articles focusing on topics of fasting practice to curb promiscuous sex. Data gathered were grouped into codes, categories, and themes. Fasting is not just about suppressing hunger and thirst but includes restraining the self from doing things that are forbidden in Islam. Interestingly, the practice of fasting in Islam helped shaped human sexual behavior through the formation of spiritual, physiological and psychological aspects. The findings can be utilized by stakeholders especially in formulating rehabilitation modules for cases of promiscuous sex.